Cultural Prejudice against Female’s Bodies in Discriminative Local Regulations: Politicization of Religion and Women - NFN Indraswari (Jurnal Perempuan, 2014)
This article discusses three main issues i.e. women, politics of identity and religion as well as the relationship among them. The three are binded by cultural prejudice casted upon female bodies, specifically in discriminatory by-laws in 342 regions in Indonesia. The discussion takes place within the framework of Indonesia’s decentralization which has been marked with among other the implementation of public policies which targeting women’s bodies and behavior in the name of morality and religion. The cultural notion is also discussed to provide a better understanding on the complexity of the relationship among the three issues as previously mentioned. This study shows that religion has been used and politicized to ostricised women’s rights and other minorities’ and vulnerable groups’ rights.